Upaya Pengembangan Sumber Daya Manusia dalam Meningkatkan Kinerja Pegawai di Kantor Desa Ombolata Simenari Kecamatan Gunungsitoli Selatan - Michael Boiman Zokho Lase; Yoel Melsaro Larosa; Eliyunus Waruwu; Ayler Beniah Ndraha (JURNAL MANAJEMEN PENDIDIKAN DAN ILMU SOSIAL, 2024)
Human resource (HR) development efforts at the Ombolata Simenari Village Office, South Gunungsitoli Sub-district, Gunungsitoli City, are an important step in improving the performance of employees who have a central role in public services and community welfare. This research aims to explore the obstacles that hinder human resource development in the village and develop recommendations to overcome these obstacles. The research method used was qualitative with a descriptive approach. Data was collected through interviews with village officials, stakeholders, and community members, as well as document analysis and secondary data. The results showed that the main constraints in human resource development in Ombolata Simenari Village include budget limitations, low employee participation in development programs, lack of access to quality training resources, and competency gaps among employees. Steps that can be taken to overcome these obstacles include adequate budget allocation, increasing employee participation, increasing access to quality training resources, and identifying and improving employee competencies. The discussion concludes that improving employee performance through HR development requires structured and sustainable steps. Organizational Development Theory and Organizational Performance Improvement Theory form the basis for designing effective HR development strategies. By overcoming existing obstacles, it is expected that employee performance at the Ombolata Simenari Village Office can improve significantly, so as to provide better services to the community and achieve the desired village development goals.